Inflammatory and oxidative stress airway markers in premature newborns of hypertensive mothers - Madoglio, R. J. [UNESP]; Rugolo, L. M. S. S. [UNESP]; Kurokawa, C. S. [UNESP]; Sa, M. P. A. [UNESP]; Lyra, J. C. [UNESP]; Antunes, L. C. O. [UNESP] (Assoc Bras Divulg Cientifica, 2016)
Although oxidative stress and inflammation are important mechanisms in the pathophysiology of preeclampsia and preterm diseases, their contribution to the respiratory prognosis of premature infants of hypertensive mothers is not known. Our objective was to determine the levels of oxidative stress and inflammation markers in the airways of premature infants born to hypertensive and normotensive mothers, in the first 72 h of life, and to investigate whether they are predictors of bronchopulmonary dysplasia (BPD)/death. This was a prospective study with premature infants less than 34 weeks' gestation on respiratory support who were stratified into 2 groups: 32 premature infants of hypertensive mothers and 41 of normotensive women, with a mean gestational age of 29 weeks. Exclusion criteria were as follows: diabetes mellitus, chorioamnionitis, malformation, congenital infection, and death within 24 h after birth. The outcome of interest was BPD/death. Malondialdehyde (MDA), nitric oxide (NO), and interleukin 8 (IL-8) were measured in airway aspirates from the first and third days of life and did not differ between the groups. Univariate and multivariate statistical analyses were performed. The concentrations of MDA, NO, and IL-8 were not predictors of BPD/death. Premature infants who developed BPD/death had higher levels of IL-8 in the first days of life. The gestational age, mechanical ventilation, and a small size for gestational age were risk factors for BPD/death. In conclusion, the biomarkers evaluated were not increased in premature infants of hypertensive mothers and were not predictors of BPD/death.
Keywords: Infant; Premature; Pre-eclampsia; Oxidative stress; Cytokines; Bronchopulmonary dysplasia